Economic Inequality Increases Status Anxiety Through Perceived Contextual Competitiveness - Melita, Davide; Willis, Guillermo B.; Rodríguez-Bailón, Rosa (Frontiers in Psychology, 2021)
Status anxiety, the constant concern about individuals’ position on the social ladder, negatively affects social cohesion, health and wellbeing (e.g. chronic stress). Given previous findings showing that status anxiety is associated with economic inequality, we aimed in this research to test this association experimentally. A cross-sectional study (Study 1) was run in order to discard confounding effects of the relationship between perceived economic inequality and status anxiety, and to explore the mediating role of a competitive climate (N=297). Then we predicted that people assigned to a condition of high inequality would perceive more status anxiety in their social context, and they would themselves report higher status anxiety. Thus, in an experimental study (Study 2) perceived economic inequality was manipulated (N=200). In Study 1, perceived economic inequality uniquely predicted status anxiety, and perceived competitiveness mediated the relationship. In Study 2 perceived economic inequality increased perceived contextual status anxiety, a specific form of perceived competitiveness based on socioeconomic status. Moreover, preliminary evidence of an indirect effect was found from perceived economic inequality to personal status anxiety, through (higher) perceived contextual status anxiety. These preliminary findings provide experimental evidence for the effects of economic inequality on status anxiety and the mechanism involved. Economic inequality makes people feel that they live in a society where they are constantly concerned and competing with each other for their socioeconomic status. These results could have important implications as health and wellbeing could be promoted by reducing economic inequalities and the competitive and materialistic environments of our societies.